Penggunaan SWAY Sebagai Media Bahan Ajar Sejarah untuk Meningkatkan TPACK Guru - Five Sri Handayani (Proceedings Series on Social Sciences & Humanities, 2023)
History lessons often become boring lessons because teachers often use one-way lecture methods, so learning becomes monotonous and makes students bored. Increasing teacher competence in mastering TPACK is expected to increase interaction and get students to learn history. Sway is an application contained in one of the Microsoft 365 features in the form of multimodal text, combining text, images, and videos. It can even be integrated with other applications through YouTube links, quizzes, or other forms of tests.